PENGEMBANGAN APLIKASI MOBILE LAYANAN PARIWISATA LOKAL SULAWESI BARAT MENGGUNAKAN FRAMEWORK FLUTTER - Sultan Jorgi; Asmawati S; Nuralamsah Zulkarnaim (Universitas Nusa Cendana, 2022)
One of the provinces in eastern Indonesia, namely West Sulawesi, has many types of tourist attractions. Many of these tourism objects have not been managed optimally by the managers or the government. Currently, there is still no available information platform that can provide detailed information regarding local tourism services available in West Sulawesi Province. This study aims to create an application product that can make it easier for tourists who will visit to find information on local tourism in West Sulawesi. Waterfall is a systematic and sequential application development method at each stage starting from the analysis stage to the implementation stage. Flutter is used as a framework for mobile application development that makes it easy to create application user interfaces. This application has succeeded in providing information related to local tourism services in West Sulawesi Province according to actual data from tourism services. Based on Alpha and Betha testing using the BlackBox method, the results in the Alpha test were that there were no functionality errors in the application, while the Betha test which was carried out directly to the user obtained the results that the application had an attractive appearance, was easy to use, informative, quite easy to understand and useful for users.